4+t=3t-18

Simple and best practice solution for 4+t=3t-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+t=3t-18 equation:


t in (-oo:+oo)

t+4 = 3*t-18 // - 3*t-18

t-(3*t)+4+18 = 0

t-3*t+4+18 = 0

22-2*t = 0 // - 22

-2*t = -22 // : -2

t = -22/(-2)

t = 11

t = 11

See similar equations:

| -2w+7=2w-29 | | n+2=-46-5n | | 7/8*5=b | | -6m-10=-19+3m | | 4x+8=4+3x | | 6t+8=18+7t | | 10-2x=x-26 | | 3+5a=-4a+84 | | 6k+10=43+3k | | 4k+2=32+7k | | 3d+5=33-d | | 6m+4=5m+4 | | -7x+9=7x-145 | | -13+5+x=-4+15 | | 2x/4x^2-2x | | 2d+5=-7d-94 | | -2-7a=3a-112 | | 6+2d=5d+6 | | 7x+1=6x+5 | | -7t-10=6t-166 | | -9+a=5a-5 | | 5m+7=6x | | -3+3k=4k-13 | | 5a+10=-2a+24 | | 5x+4=-20+3x | | a+5=5a-3 | | 2b-8=-8+b | | w+3=3w-17 | | 2w-1=-19+4w | | 18=3(3*-6) | | 5(x-2)=3(x+1) | | -m+9=5m-45 |

Equations solver categories